Recovery analysis for adaptive learning from non-stationary data streams: Experimental design and case study - Shaker, A.; Hüllermeier, Eyke (Neurocomputing)

Directly comparing entanglement-enhancing non-Gaussian operations - Bartley, Tim; Walmsley, Ian A (New Journal of Physics)

Multi-axial Material Testing at High Strain Rates in High Speed Cupping Tests - Weiß Borkowski, Nathalie; Marten, Thorsten; Block, Holger; Tröster, Thomas

Bestimmung und Optimierung von Eigenspannungen in hybriden Werkstoffsystemen aus Metall und Faserverbundkunststoff (FVK) - Frantz, M.; Lauter, C.; Wang, Z.; Tröster, Thomas

Kennwertermittlung an Faserverbundkunststoffen für Crashsimulationen mit dem FE-Solver LS-Dyna - Reuter, C.; Tröster, Thomas; Lauter, C.

Fatigue life prediction for metals processed by Selective Laser Melting using finite element analyses - Reschetnik, W.; Leuders, S.; Riemer, A.; Tröster, Thomas; Richard, H. A.; Niendorf, T.

Intrinsic Manufacturing of Metal-FRP-Hybrid Structural Automotive Components by Resin Transfer Moulding - Wang, Z.; Lauter, C.; Sanitther, B.; Frantz, M.; Tröster, Thomas

Methodology for the Product Engineering of Lightweight Structures in Multi-Material Design - Lauter, C.; Wang, Z.; Tröster, Thomas; Brandis, R.; Köchling, D.

Fatigue Behaviour of a Structural Component Manufactured by Selective Laser Melting and Investment Casting - Leuders, S.; Meiners, S.; Taube, A.; Tröster, Thomas; Niendorf, T.

Material follows form follows function - Wingenbach, Nils; Tröster, Thomas

Efficient Biomimetic Hydroxylation Catalysis with a Bis(pyrazolyl)imidazolylmethane Copper Peroxide Complex - Wilfer, Claudia; Liebhäuser, Patricia; Hoffmann, Alexander; Erdmann, Hannes; Grossmann, Oleg; Runtsch, Leander; Paffenholz, Eva; Schepper, Rahel; Dick, Regina; Bauer, Matthias; Dürr, Maximilian; Ivanović-Burmazović, Ivana; et al. (Chemistry - A European Journal)

Dynamic network reconfiguration in wireless DenseNets with the CROWD SDN architecture - Auroux, Sébastien; Draxler, Martin; Morelli, Arianna; Mancuso, Vincenzo (2015 European Conference on Networks and Communications (EuCNC))

MCB – A multi-channel beaconing protocol - Klingler, Florian; Dressler, Falko; Cao, Jiannong; Sommer, Christoph (Ad Hoc Networks)

Linear and Competitive Strategies for Continuous Robot Formation Problems - Degener, Bastian; Kempkes, Barbara; Kling, Peter; Meyer auf der Heide, Friedhelm (ACM Transactions on Parallel Computing)

Towards Gathering Robots with Limited View in Linear Time: The Closed Chain Case - Abshoff, Sebastian; Andreas Cord-Landwehr, Andreas; Jung, Daniel; Meyer auf der Heide, Friedhelm (ArXiv: 1501.04877)
In the gathering problem, n autonomous robots have to meet on a single point. We consider the gathering of a closed chain of point-shaped, anonymous robots on a grid. The robots only have local knowledge about a constant number of neighboring robots along the chain in both directions. Actions are performed in the fully synchronous time model FSYNC. Every robot has a limited memory that may contain one timestamp of the global clock, also visible to its direct neighbors. In this synchronous time model, there is no limited view gathering algorithm known to perform better than in quadratic runtime. The configurations that show the quadratic lower bound are closed chains. In this paper, we present the first sub-quadratic---in fact linear time---gathering algorithm for closed chains on a grid.

Analyse integral erfasster rotationssymmetrischer Schallwechseldruckverteilungen in Schlierenabbildungen - Olfert, Sergei; Henning, Bernd

On the optimal configuration of triple-ring-electrodes on piezoceramic transducers towards increased parameter sensitivity of impedance - Kulshreshtha, Kshitij; Jurgelucks, Benjamin; Bause, Fabian; Rautenberg, Jens; Unverzagt, Carsten

Analyse integral erfasster Schallwechseldruckverteilungen in Schlierenabbildungen - Olfert, Sergei; Henning, Bernd (XXIX Messtechnisches Symposium)

On the optimal configuration of triple-ring-electrodes on piezoceramic transducers towards increased parameter sensitivity of impedance - Jurgelucks, Benjamin; Kulshreshtha, Kshitij; Bause, Fabian; Rautenberg, Jens; Unverzagt, Carsten

Model based sensitivity analysis in the determination of viscoelastic material properties using transmission measurements through circular waveguides - Bause, Fabian; Gravenkamp, Hauke; Rautenberg, Jens; Henning, Bernd
Several ultrasonic approaches for material determination are formulated in terms of an (nonlinear) inverse problem, e.g. immersion technique (Castaings et al. (2000)) or plate-waveguide techniques (Marzani et al. (2012)). In this contribution we focus on cylindrical waveguides for ultrasonic material determination and especially on the sensitivity of recorded transmission signals to the material properties. We utilize composite scaled sensitivities to determine the information content that can be achieved by the setup to certain parameters and discuss the limitations of the approach.
Keywords: Sensitivity inverse problem ultrasonic material determination